(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Folk medicine recommends medicinal herbs with antihypoxic properties for the respiratory system diseases such as bronchitis, bronchial asthma, cold. One of these herbs is Trifolium pratense L. Fam. Fabaceae. The animals fed by trifolium flowers could stand hypoxia on the altitude 7–8 thousand m. The experiment results suggest that the increase of organism stability happens both on the system (external respiration remains longer) and cell levels since simultaneously registered electrical activity of the respiratory centre neurons of medulla has shown high stability compared to screening group.